Multi-omics identify ribosome related causal genes methylation, splicing, and expression in prostate cancer - Chengcheng Wei; Jingke He; Yunfan Li; Yu Luo; Liangdong Song; Kun Han; Jindong Zhang; Shuai Su; Delin Wang (Discover Oncology)
Abstract Background Understanding the molecular underpinnings of prostate cancer remains a critical challenge in oncology. Ribosomes, essential cellular organelles responsible for protein synthesis, have emerged as potential regulators in cancer development. Previous studies suggest that dysfunction in ribosomal processes may contribute significantly to prostate cancer progression. We used summary-data-based Mendelian randomization (SMR) and colocalization analysis, as well as single-cell analysis, to investigate the association between ribosome-related genes and prostate cancer by integrating multi-omics. Method In this study, we employed a multi-omics approach integrating genomics and transcriptomics data to investigate the role of ribosome-related genes in prostate cancer. Summary-level data for prostate cancer were obtained from The Prostate Cancer Association Group to Investigate Cancer Associated Alterations in the Genome and FinnGen studies. SMR analyses were performed to assess the relevance of ribosomal gene-related molecular signatures to prostate cancer. We further performed colocalization analysis to assess whether the identified signal pairs shared causal genetic variants. Genes were then validated with single-cell sequencing analysis. Results We identified significant causal effects of ribosome gene methylation on prostate cancer. After integrating the multi-omics data of mQTL, sQTL and eQTL, we identified two ribosomal genes, NSUN4 and MPHOSPH6. Methylation and splicing at different sites on the NSUN4 gene showed increased and decreased risks for prostate cancer, indicating complex gene regulation mechanisms. For instance, NSUN4 methylation site of cg10215817 was genetically associated with the increased prostate cancer risk (OR 1.20, 95% CI 1.10,1.30), while NSUN4 methylation site of cg00937489 was genetically associated with the decreased prostate cancer risk (OR 0.84, 95% CI 0.74,0.94); NSUN4 chr1:46341497:46344801 splicing (OR 1.11, 95% CI 1.05–1.17) were positively associated with prostate cancer risk, while NSUN4 chr1:46340919:46344801 splicing (OR 0.95, 95% CI 0.92–0.97) were negatively associated with prostate cancer risk. Expression analysis indicated significant associations between prostate cancer risk and increased expression levels of NSUN4 (OR 1.06, 95% CI 1.03–1.09; PPH4 = 0.79) and MPHOSPH6 (OR 1.07, 95% CI 1.04–1.10; PPH4 = 0.70). In-depth single-cell analysis showed that NSUN4 highly expresses in epithelial cells, while MPHOSPH6 highly expresses in myeloid cells. Conclusion The study found that ribosome NSUN4 and MPHOSPH6 genes were associated with prostate cancer risk. This integrative multi-omics study underscores the significance of ribosome-related genes in prostate cancer etiology. By elucidating the molecular mechanisms underlying ribosome dysfunction, our research identifies potential therapeutic targets for mitigating disease progression. These findings not only enhance our understanding of prostate cancer biology but also pave the way for personalized therapeutic strategies targeting ribosomal pathways to improve clinical outcomes.